Delivery Models and Health Economics of Supportive Care Services in England: A Multicentre Analysis. Issue 6 (June 2023) - Monnery, D.; Tredgett, K.; Hooper, D.; Barringer, G.; Munton, A.; Thomas, M.; Vijeratnam, N.; Godfrey, N.; Summerfield, L.; Hawkes, K.; Staley, P.; Holyhead, K.; et al.
Abstract: Aims: Improvements in cancer treatment have led to more people living with and beyond cancer. These patients have symptom and support needs unmet by current services. The development of enhanced supportive care (ESC) services may meet the longitudinal care needs of these patients, including at the end of life. This study aimed to determine the impact and health economic benefits of ESC for patients living with treatable but not curable cancer. Materials and methods: A prospective observational evaluation was undertaken over 12 months across eight cancer centres in England. ESC service design and costs were recorded. Data relating to patients' symptom burden were collected using the Integrated Palliative Care Outcome Scale (IPOS). For patients in the last year of life, secondary care use was compared against an NHS England published benchmark. Results: In total, 4594 patients were seen by ESC services, of whom 1061 died during follow-up. Mean IPOS scores improved across all tumour groups. In total, £1, 676, 044 was spent delivering ESC across the eight centres. Reductions in secondary care usage for the 1061 patients who died saved a total of £8, 490, 581. Conclusions: People living with cancer suffer with complex and unmet needs. ESC services appear to be effective at supporting these vulnerable people and significantly reduce the costs of their care. Highlights: The first multicentre UK-based study examining the impact and cost-utility of supportive care services in cancer. Enhanced supportive care models improve symptoms burden and relieve pressure on secondary care. If offered to all patients with treatable but not curable cancer, the costs saved from secondary care avoidance in the last 12 months of life for those who die more than pays for the cost of supportive care for everyone.